Hubungan Self Assessment Dengan Kompetensi Klinik Mahasiswa Kedokteran - Novitasari, Andra; Djunaidi, Djunaidi (Universitas Muhammadiyah Semarang, 2015)
Relationship between Self Assessment and Clinical Competence of Medical StudentsBackground: One area of competence that must be possessed by a doctor is introspection and self-development. Self-assessment is an important component in self-development. Students who have been able to carry out self-assessment on one component of clinical competence well are not necessarily able to carry out self-assessment by integrating all components of clinical competence.Objective: This study aims to analyze the relationship between self-assessment and clinical competence of medical students.Methods: This study is an observational study with a cross sectional design which was analyzed by statistical tests which included univariate analysis and bivariate analysis of the variables between the existence of self-assessment and clinical competence of medical students. The sample in this study was 60 7th semester medical students. Sampling was done by consecutive sampling technique.Results: Bivariate analysis using Chi-Square test showed that there was no significant relationship between self-assessment and clinical competence of medical students (p=0.643).Conclusion: Self-assessment of clinical competence has not been able to provide an overview of the actual clinical competence possessed by students Latar Belakang: Salah satu area kompetensi yang harus dimiliki oleh seorang dokter adalah mawas diri dan pengembangan diri. Self assessment merupakan komponen penting dalam pengembangan diri. Mahasiswa yang sudah mampu melakukan self assessment pada satu komponen kompetensi klinik dengan baik, belum tentu mampu melakukan self assessment dengan mengintegrasikan seluruh komponen kompetensi klinik. Tujuan: Penelitian ini bertujuan untuk menganalisis hubungan antara self assessment dengan kompetensi klinik mahasiswa kedokteran. Metode Penelitian: Penelitian ini merupakan studi observasional dengan desain cross sectional yang dianalisis dengan uji statistik yang meliputi analisis univariat, dan analisis bivariat terhadap variabel antara adanya self assessment dan kompetensi klinik mahasiswa kedokteran. Sampel dalam penelitian ini sebanyak 60 mahasiswa kedokteran semester ke-7. Pengambilan sampel dilakukan dengan teknik consecutive sampling. Hasil Penelitian: Analisis bivariat menggunakan uji Chi-Square menunjukkan bahwa tidak ada hubungan yang signifikan antara self assessmen dan kompetensi klinik mahasiswa kedokteran (p=0.643). Kesimpulan: Self assessment terhadap kompetensi klinik belum dapat memberikan gambaran kompetensi klinik yang sebenarnya dimiliki oleh mahasiswa